(untitled) (Pharmacy Essentials: A Compact Guide for Students and Practitioners, 2025)
Author Dr. Ajmal Tariq Hussain, Assistant Professor, Department of Pharmacy Practice, Amity Institute of Pharmacy, Amity University, Lucknow, India Abstract Clinical pharmacy practice applies pharmaceutical science to optimize medication therapy outcomes through direct patient care activities across healthcare settings. Patient assessment establishes the foundation for clinical decision-making through systematic collection and interpretation of subjective information, physical findings, laboratory data, and medication histories, identifying drug-related problems requiring intervention. Therapeutic drug monitoring applies pharmacokinetic principles to medications with narrow therapeutic indices, using serum concentration measurements to guide individualized dosing adjustments that maximize efficacy while minimizing toxicity for agents including anticonvulsants, aminoglycosides, and immunosuppressants. Care plans translate assessment findings into structured interventions with clear, measurable goals addressing identified medication-related problems through evidence-based strategies, appropriate monitoring parameters, and follow-up timelines communicated across healthcare teams. Medication therapy management encompasses comprehensive services optimizing therapeutic outcomes through systematic medication review, identification of drug-related problems, development of personalized care plans, intervention implementation, and documentation, with particular focus on complex patients with multiple chronic conditions. The principles of clinical pharmacy practice improve patient outcomes by ensuring appropriate medication selection, optimizing dosing regimens, enhancing adherence, preventing adverse effects, and reducing healthcare costs through prevention of medication-related complications. Keywords: Medication Optimization; Clinical Decision-Making; Patient-Specific Therapy; Evidence-Based Practice; Therapeutic Outcomes VIEW PDF